Diversity and Growth Behaviour of Nepenthes (Pitcher Plants) in Tanjung Puting National Park, Central Kalimantan Province - TRI HANDAYANI; DIAN LATIFAH; DODO DODO (Biodiversitas Journal of Biological Diversity, 2005)
Nepenthes is one of the popular genus of pitcher plants. Research on the biodiversity and growth beharviour of Nepenthes spp. in Tanjung Puting National Park was carried out. There were four species studied, namely: N. ampullaria, N. mirabilis N. rafflesiana, and N. x. hookeriana,. There were about 2096 individuals recorded in this study consisting of 1322 N. ampullaria, 1332 N. mirabilis, 141 N. rafflesiana, and 111 N. x. hookeriana. Variation of tendril positions occurred in 1 rosette plant and 3 climbing stems (mature plants) of N. ampullaria, 2 rosettes and 9 mature N. mirabilis, 1 rosette and 4 mature N. rafflesiana, 2 rosettes and 2 mature N. x. hookeriana. Their habitats were also very specific. It was noted that 6 species of other plants were grown and associated with the Nepenthes spp.Key words: biodiversity, growth beharviour, Nepenthes ampullaria, Nepenthes mirabilis, Nepenthes rafflesiana, Nepenthes x hokeriana, Tanjung Puting National Park.